You're correct, the answer is C.
Given any function of the form
, then the derivative of y with respect to x (
) is written as:
In which
is any constant, this is called the power rule for differentiation.
For this example we have
, first lets get rid of the quotient and write the expression in the form
:
Now we can directly apply the rule stated at the beginning (in which
):
Note that whenever we differentiate a function, we simply "ignore" the constants (we take them out of the derivative).
Answer:
Step-by-step explanation:
-5x+31+3x=3
move everthing to one side
-5+31+3x-3=0
add and subtract common terms
-2x+28=0
divide across by common denominator
-x+14=0
Solve for x
x=14
7x +33 < 26 isolate the term with a variable by subtracting 33
7x < -7 divide by 7
x < -1
Answer:
69 centimeters squared
Step-by-step explanation:
First, find the area of the big square = 11cm * 4cm = 44cm
Next, find the area of the leftover square = 5cm * 5cm =25cm
Add them together to get 69 centimeters squared
Hopefully this helps - let me know if you have any questions!
Answer:
-x^5 - 7x^4 + x^2 + (1/8)x - 9
Step-by-step explanation:
Rewrite the given -9+1/8x-7x^4+x^2-x^5 in descending order of the variable x:
-9+1/8x
-x^5 - 7x^4 + x^2 + (1/8)x - 9